Primary Sjögren's syndrome without ocular involvement: A rare case report - Tushar Phulambrikar; Priya Pande; Siddharth Singh; Shali Magar (Wolters Kluwer Medknow Publications, 2014)
Sjögren's Syndrome (SS) is a chronic systemic autoimmune disorder, characterized by the lymphocytic infiltration of lacrimal and salivary glands, giving rise to dry eyes (keratoconjunctivitis sicca) and dry mouth (xerostomia). Primary Sjögren's Syndrome commonly presents only with sicca manifestations; whereas, secondary Sjögren's syndrome occurs in connection with other autoimmune rheumatic diseases. Primary Sjögren's syndrome without ocular manifestation is rarely reported in the literature. Here we report a case of a 45-year-old female, who presented to us with complaints of dryness of mouth and dysphagia, without any ocular and systemic manifestations. On further evaluation she was diagnosed as a case of Primary Sjögren's syndrome. With this case report, we intend to emphasize the importance of an early diagnosis of this disorder, along with a brief review of various diagnostic criteria.